MicroRNA-155 confers encephalogenic potential to Th17 cells by promoting effector gene expression - Hu, Ruozhen (2013)
Th17 cells are central to the pathogenesis of autoimmune disease, and recently specific noncoding microRNAs (miRNAs) have been shown to regulate their development. However, it remains unclear if miRNAs are also involved in modulating Th17 cell effector functions. Consequently, we examined the role of miR-155 in differentiated Th17 cells during their induction of Experimental Autoimmune Encephalomyelitis (EAE). Using adoptive transfer experiments, we found that highly purified, MOG antigen-specific Th17 cells lacking miR-155 were defective in their capacity to cause EAE. Gene expression profiling of purified miR-155−/− IL-17F+ Th17 cells identified a subset of effector genes that are dependent upon miR-155 for their proper expression through a mechanism involving repression of the transcription factor Ets1. Among the genes reduced in the absence of miR-155 was IL-23R, resulting in miR-155−/− Th17 cells being hypo-responsive to IL-23. Taken together, our study demonstrates a critical role for miR-155 in Th17 cells as they unleash autoimmune inflammation, and finds that this occurs through a signaling network involving miR-155, Ets1 and the clinically relevant IL-23-IL-23R pathway.